2013
DOI: 10.1088/1742-6596/442/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Entropy of conditional tomographic probability distributions for classical and quantum systems

Abstract: Abstract. The possibility to describe hybrid systems containing classical and quantum subsystems by means of conditional tomographic probability distributions (tomograms) is discussed. Tomographic Shannon and Rényi entropies associated with the tomograms are studied, and new tomographic uncertainty relations are obtained. IntroductionThe possibility to describe the hybrid systems containing both classical and quantum subsystems was considered, for example, in [1][2][3][4][5]. The problems presented in the proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Since there exists the strong subadditivity condition for the density matrix of the three-partite system [23], we can obtain a new matrix inequality, which is an analog of this condition, for an arbitrary Hermitian N ×N matrix, including the density matrix of the single qudit state. We continue the consideration of the found matrix inequalities in the form of relations for qudit tomograms of classical and quantum system states [37][38][39][40], empolying the inequalities for the probability vectors depending on the parameters of the unitary matrix in a future publication.…”
Section: Discussionmentioning
confidence: 99%
“…Since there exists the strong subadditivity condition for the density matrix of the three-partite system [23], we can obtain a new matrix inequality, which is an analog of this condition, for an arbitrary Hermitian N ×N matrix, including the density matrix of the single qudit state. We continue the consideration of the found matrix inequalities in the form of relations for qudit tomograms of classical and quantum system states [37][38][39][40], empolying the inequalities for the probability vectors depending on the parameters of the unitary matrix in a future publication.…”
Section: Discussionmentioning
confidence: 99%
“…As we have discussed in [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], one can consider probability distributions of composite and noncomposite systems as a set of N nonnegative numbers; in the case of N = N 1 N 2 or N = N 1 N 2 N 3 , where N 1 , N 2 , and N 3 are integers, one can obtain new entropy-information relations for noncomposite systems. Analogously, for quantum indivisible systems, one can obtain the relations for entropy and information analogous to the relations known for multiqudit systems.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, multilevel (i.e., noncomposite) quantum systems attracted a significant deal of interest as a potential platform for quantum technologies [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. On the one hand, such multilevel quantum systems can be realized using a single physical system, e.g., multilevel superconducting artificial atoms [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Speaking in terms of the quantum Shannon theory [1], one can establish a direct correspondence between information and entropic measures for composite and noncomposite quantum systems. Comprehensive studies of information and entropic characteristics of noncomposite quantum system demonstrated their resource for information processing [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. In particular, the single qudit version of the Deutsch algorithm using through anharmonic superconducting multilevel artificial atom has been suggested [10].…”
Section: Introductionmentioning
confidence: 99%